Achievement to urban sustainable form - S. , Zarabadi; N. , Karimi (2008)
City and urban form is sustainable when a city is accessible in its total aspect for its residents. In other words, a sustainable city necessitates circumstances which are changing after passing time. This paper is aimed by answering the following questions: What is urban sustainable form? How is the level of city sustainability related to its form, size, density and structure? The especial structure of historical city of Yazd as in central Iran is originated from its location at the desert margin. Also, Zagros heights prevent the city from sea humidity and many other factors which cause weather dryness and lack of step in Yazd city. But in the past the creative designers of the city utilized from modular concept in the form and the size of building, compatible with climate, the maximum use of potential and local materials. Also they had avoided their designs from unnecessary decoration by using ornaments including aesthetic and function aspect. They considered human scale in proper form based on resolving human need during time to create an urban sustainable form too. This paper is attempting to recognize urban sustainable model by identifying the principles and concepts of sustainable design in Yazd old fabric. So, the urban structure and its component elements are categorized in three level of macro, medium and micro. After classification its obvious specification in different level from the whole to detail and vice versa, it can be analyzed to present the hidden model in Yazd city in which urban sustainable form follows them. The obtained pattern can developed during a creative process and utilize it in future city design.